2014
DOI: 10.1099/vir.0.057521-0
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic variation of foot-and-mouth disease virus serotype A

Abstract: The current measures to control foot-and-mouth disease (FMD) include vaccination, movement control and slaughter of infected or susceptible animals. One of the difficulties in controlling FMD by vaccination arises due to the substantial diversity found among the seven serotypes of FMD virus (FMDV) and the strains within these serotypes. Therefore, vaccination using a single vaccine strain may not fully cross-protect against all strains within that serotype, and therefore selection of appropriate vaccines requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…The genetic diversity in the P1-coding region within the SAT serotypes is reflected in the antigenic properties of these viruses; therefore, there are implications for the selection of vaccine strains that would provide the best vaccine match against emerging viruses (15). In the antigenically diverse FMDV serotype A strains, predicting antigenic differences using genetic sequences alone does not provide reliable information for vaccine matching (16). Therefore, others have added structural information on the location of the amino acid sequence in the virus to the sequence data and have shown that it was a powerful tool for predicting antigenic relationships and has the potential to be applied to a variety of different infectious agents (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic diversity in the P1-coding region within the SAT serotypes is reflected in the antigenic properties of these viruses; therefore, there are implications for the selection of vaccine strains that would provide the best vaccine match against emerging viruses (15). In the antigenically diverse FMDV serotype A strains, predicting antigenic differences using genetic sequences alone does not provide reliable information for vaccine matching (16). Therefore, others have added structural information on the location of the amino acid sequence in the virus to the sequence data and have shown that it was a powerful tool for predicting antigenic relationships and has the potential to be applied to a variety of different infectious agents (17).…”
mentioning
confidence: 99%
“…They showed that the r 1 value did not predict cross-protection. Other authors have linked genetic information to cross-reactions in serology (15)(16)(17) and have showed that the r 1 value can be predicted from surface-exposed amino acid changes. These studies did not address the inherent variability of the r 1 value, and it is therefore important to have a more comprehensive view on the usefulness of r 1 values using results generated with various FMDV strains in one laboratory.…”
mentioning
confidence: 99%
“…Active economic and trade relations between RK and surrounding countries as well as uncontrolled transboundary movement of wild animals could have resulted in importation of A 22 lineage into RK. The A 22 lineage is somewhat antigenically distinct from serotype A resident lineages (Ludi et al., ). Thus, the vaccine used in RK at the time of A 22 's introduction may not have provided adequate protection, leading to greater disease spread.…”
Section: Discussionmentioning
confidence: 99%
“…For each individual cow in the heterologous potency test, the results of the 3 week post-vaccination sera were used to calculate the r 1 -value [15]. Subsequently, the r 1 -values were log transformed to calculate the geometric mean, standard deviation and 95% CI.…”
Section: R 1 -Value Determinationmentioning
confidence: 99%